Kontribusi Pendidikan Islam Terhadap Perempuan dan Feminisme - Fathurrossi Fathurrossi (PSGA LP2M IAIN Pontianak, 2017)
Islamic Education has a great goal to create wonderfu civilization that has intellectual and religious ability based on the aims of Islamic Education itself. Because, without the exact aim of Islamic Education, so the methods used would not be based on Islam itself. Moreover, the Islamic Education aims to guide, create, and develop humans to be Allah’s followers that have incredible beliefs, especially women who are created to be special creatures.